The Impact of Edentulism on Oral and General Health - Elham Emami; Raphael Freitas de Souza; Marla Kabawat; Jocelyne S. Feine (Hindawi Limited, 2013)
An adequate dentition is of importance for well-being and life quality. Despite advances in preventive dentistry, edentulism is still a major public health problem worldwide. In this narrative review, we provide a perspective on the pathways that link oral to general health. A better understanding of disease indicators is necessary for establishing a solid strategy through an organized oral health care system to prevent and treat this morbid chronic condition.